Evaluation of the Immunochromatographic NG-Test Carba 5, RESIST-5 O.O.K.N.V., and IMP K-SeT for Rapid Detection of KPC-, NDM-, IMP-, VIM-type, and OXA-48-like Carbapenemase Among Enterobacterales - Han, Renru; Guo, Yan; Peng, Mingjia; Shi, Qingyu; Wu, Shi; Yang, Yang; Zheng, Yonggui; Yin, Dandan; Hu, Fupin (Frontiers in Microbiology, 2021)
Background Enterobacterales are the most common pathogens for nosocomial infections. The emergence and spread of KPC, NDM, and OXA-48-like carbapenemase-producing Enterobacterales with their extensively drug-resistant characteristics have posed great threats to public health. This study aimed to evaluate the performance of NG-test Carba 5, RESIST-5 O.O.K.N.V., and IMP K-SeT for rapid detection of five carbapenemases (KPC, NDM, VIM, IMP, and OXA-48-like) among Enterobacterales. Methods A total of 186 carbapenem-resistant Enterobacterales clinical isolates and 29 reference strains were used in this study. Carbapenemase genes were confirmed by PCR and DNA sequencing. The sensitivities and specificities of these assays were calculated utilizing the VassarStats software. Results For clinical isolates, the NG-test Carba 5 detected KPC, NDM, OXA-48-like, IMP, and VIM in less than 15 min with the sensitivity and specificity of 100% and 100%, respectively. The RESIST-5 O.O.K.N.V. detected KPC, NDM, OXA-48-like, and VIM with the sensitivity and specificity of 99.4 and 100%. The IMP K-SeT detected all of the IMP producers (6/6). For reference strains, the sensitivity and specificity of NG-test Carba 5, RESIST-5 O.O.K.N.V., and IMP K-SeT were all 100 and 100%, respectively. Conclusion As efficient, rapid, and convenient diagnostic methods, NG-test Carba 5, RESIST-5 O.O.K.N.V., and IMP K-SeT could help to simplify the complex routine workflow for detecting carbapenemases. Rapid and accurate identification of carbapenemase is of significance for both epidemiological and infection control purposes.